Optimizing plug-in electric vehicle charging in interaction with a small office building - Ilan Momber; David Dallinger; Sebastian Beer; Tomás Gomez; Martin Wietschel (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2011)
This paper considers the integration of plug-in electric vehicles (PEVs) in micro-grids. Extending a theoretical framework for mobile storage connection, the economic analysis here turns to the interactions of commuters and their driving behavior with office buildings. An illustrative example for a real office building is reported. The chosen system includes solar thermal, photovoltaic, combined heat and power generation as well as an array of plug-in electric vehicles with a combined aggregated capaci-ty of 864 kWh. With the benefit-sharing mechanism proposed here and idea-lized circumstances, estimated cost savings of 5% are possible. Different pricing schemes were applied which include flat rates, demand charges, as well as hourly variable final customer tariffs and their effects on the operation of intermittent storage were revealed and examined in detail. Because the plug-in electric vehicle connection coincides with peak heat and electricity loads as well as solar radiation, it is possible to shift energy demand as desired in order to realize cost savings.
urn:nbn:de:0011-n-1783473
Keywords: 330; Battery storage; building management systems; dispersed storage and generation; electric vehicles; load management; microgrid; optimization methods; power system economics; road vehicle electric propulsion